PENGEMBANGAN HERBARIUM TUMBUHAN YANG DIGUNAKAN DALAM UPACARA ADAT TINGKEBAN DI KABUPATEN JOMBANG - Subiyanto, Ardip; Ami, Mucharommah Sartika (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to determine the results of the validation of herbarium experts and learning media experts on the developed plant herbarium. The types of plants used as herbarium specimens are plants used in the Tingkeban traditional ceremony carried out by the community in Jombang Regency. This research is a development research that refers to the R&D model which consists of 10 stages, but only the first five stages were carried out in this study. The five stages are potential and problems, information gathering, product design, design validation, and design improvement. The instruments used are interview guides and validation sheets that are adjusted to the expertise of each validator. There are two validation sheets used, namely the herbarium expert validation sheet and the learning media expert validation sheet. The data that has been collected was analyzed descriptively. The results showed that the developed herbarium obtained a score of 80 with the criteria quite feasible from the herbarium expert, and obtained a score of 95 with the criteria very feasible from the learning media expert. This shows that the herbarium developed can be used as a medium for learning biology, after going through a process of improvement based on suggestions from the two validators.